Credence Goods Markets with Heterogeneous Experts - Heinzel, Joachim Maria Josef
In this paper, we analyze a credence goods model adjusted to the health care market with regulated prices and heterogeneous experts. Experts are physicians and are assumed to differ in their cost of treating a small problem. We investigate the effects of this heterogeneity on the physicians’ level of fraud and on the patients’ search for second opinions. We find that introducing a fraction of more efficient low-cost physicians always increases social welfare, but in some cases only because of the raised physicians’ surplus. When the low-cost physicians’ cost advantage is small, imposing a share of low-cost physicians does not change the equilibrium fraud level. When the cost advantage is large, however, different changes in the fraud level occur depending on the share of generated low-cost physicians, the search rate and the initial level of fraud.
Keywords: credence goods; treatment efficiency; heterogeneous experts; overcharging

Credence Goods Markets with Fair and Opportunistic Experts - Heinzel, Joachim Maria Josef
We analyze a credence goods market adapted to a health care market with regulated prices, where physicians are heterogeneous regarding their fairness concerns. The opportunistic physicians only consider monetary incentives while the fair physicians, in addition to a monetary payoff, gain an non-monetary utility from being honest towards patients. We investigate how this heterogeneity affects the physicians’ equilibrium level of overcharging and the patients’ search for second opinions (which determines overall welfare). The impact of the heterogeneity on the fraud level is ambiguous and depends on several factors such as the size of the fairness utility, the share of fair physicians, the search level and the initial fraud level. Introducing heterogeneity does not affect the fraud or the search level when the share of fair physicians is small. However, when social welfare is not at its maximum, social welfare always increases if we introduce a sufficiently large share of fair physicians.
Keywords: credence goods; heterogeneous experts; fairness; overcharging

Bundling in a Distribution Channel with Retail Competition - Heinzel, Joachim Maria Josef
We analyze the incentives for retail bundling and the welfare effects of retail bundling in a decentralized distribution channel with two retailers and two monopolistic manufacturers. One manufacturer exclusively sells his good to one retailer, whereas the other manufacturer sells his good to both retailers. Thus, one retailer is a monopolist for one product but competes with the other retailer in the second product market. The two-product retailer has the option to bundle his goods or to sell them separately. We find that bundling aggravates the double marginalization problem for the bundling retailer. Nevertheless, when the retailers compete in prices, bundling can be more profitable than separate selling for the retailer as bundling softens the retail competition. The ultimate outcome depends on the manufacturers’ marginal costs. Given retail quantity competition, however, bundling is in no case the retailer’s best strategy. Furthermore, we show that profitable bundling reduces consumer and producer surplus in the equilibrium.
Keywords: retail bundling; leverage theory; double marginalization